BIOLEACHING OF LODAN QUARTZ USING Aspergillus ficuum - Sri Handayani (Puslitbang tekMIRA, 2017)
Depending on its purity, quartz has a wide application in industry. Fungi play an important role in the quartz purification. A bioleaching study of Lodan quartz sample from Rembang, Central Java was conducted to obtain a suitable raw material for industrial applications. The microbial process using selected-indigenous fungus of Aspergillus ficuum in terms of removing iron, aluminum, and other unwanted metals within quartz. The result was then compared to the chemical leaching using pure citric and oxalic acids. The bioleaching process removed the iron (Fe2O3) from the initial content (0.78%) in the original sand sample to reach a level of 0.013% Almost 98.3% iron was removed. The bioleaching test also removed the aluminum, manganese, chrome, and titanium to a very low level within the 12-day process. The iron content in this treated quartz met the standards for optical and high-quality glass. On the other hand, the chemical leaching using pure citric and oxalic acids concentrations were equal to those that were produced by A. ficuum could only removed 70.5% of iron around 0.23% iron and 0,29 % aluminium were still remained in the sand. This fact suggested that the bioleaching method is more effective than the chemical one using the organic acids. The use of fungi to remove iron from quartz has the potential to be an effective method for upgrading the content and the commercial value of the quartz. The experimental results of this study have provided significant opportunity to use biotechnological approach for producing the quartz as a feed material for the high-quality glass industry.